THE CORRELATION BETWEEN KNOWLEDGE AND ATTITUDES OF WOMEN OF FERTILE AGE TOWARD BREAST SELF-EXAMINATION - Susanti Susanti; Silvia Mona; Munirah Munirah; Musher Abdulwahid Aljaberi (MEDIS: Jurnal Riset Ilmu Kesehatan, 2024)
Background. Breast cancer is the most common disease suffered by women, impacting more than 1.5 million women each year and also causing the largest number of women deaths caused by cancer. In 2015, there were 507,000 women died that caused of breast cancer, which means about 15% of all cancer deaths in women were caused by breast cancer. It can be seen from women at 2.2 per 1,000 inhabitants and men at 0.6 per 1,000 inhabitants. Breast cancer is the highest percentage of new cases (43.3%) and a high percentage of mortality (1the 2.9%) of women in the world. Breast cancer tends to affect elderly women over 50 years old. There were 8-10 cases of breast cancer occurring at the age. Behavior is the action or behavior of an organism that can be observed and learned. Purpose: The research's purpose was to find out the correlation between the knowledge and attitude of women at a fertile age toward breast self-examination (BSE). Method: The instrument of the research was questionnaires. This research used Cross Sectional Design. The population was 100 of fertile age. It used Purposive Sampling and was conducted at Baloi Permai Public Health Centre Batam City in February-September 2020. The researcher used analytics to analyze data. Result: The resulting analytics that among 100 respondents, there were 72 women had good knowledge 28 women had less knowledge, 54 women had a good attitude and 46 women had a bad attitude. 54 women did a breast self-examination (BSE) and 46 women did not do a breast self-examination (BSE). Statistical test results using chi-square obtained (α) = 0.05 and p = 0.01 which means p-value< (α), it means that both variables correlate, so it can be concluded there was a correlation of knowledge and attitude of women on fertile age toward breast self-examination (BSE).